Change Management That Works : Making Impacts in Challenging Environments - Hughes, Caroline; So, Sokbunthoeun; Ariadharma, Erwin; April, Leah (World Bank, Washington, DC, 2017)
Achieving better governance has been a central problem for development. When public services are not delivered as intended, reform action becomes necessary and that involves deliberate activities to change laws, structures, and processes to improve public sector performance and benefit public service users. The key challenge is that changes in the design of the institution or its procedures do not necessarily translate into immediate changes in the behavior of relevant actors. A central problem of public sector reform is ensuring that changes in laws and policies also prompts changes in the way that people work, so that service delivery improves. There is no one-size-fits-all approach ensuring that change happens the desirable way; however, experiences from the field suggest that a useful combination of political economy analysis with change management tools can help to maximize positive impacts. Different contexts will require different approaches to change management, and therefore political economy analysis can be used productively to design a targeted change management strategy that builds on existing strengths and opportunities. Greater integration of political economy analysis into change management assessments has been helpful in deepening understanding of attitudes to change within these particular contexts. This has allowed more effective leveraging of the opportunities for reform through the more systematic tailoring of change management strategies to different sets of issues emerging among particular groups of actors. Cambodia and Indonesia, the case studies presented in the paper, help to illustrate this.